(untitled) (Research, Society and Development, 2020)
The use of smartphones during this pandemic increased rapidly. Smartphones are the most widely used communication media compared to other communication media. This is because smartphones have various features and applications that can help users in completing their work, getting entertainment, and interacting with others. However, in every technology used by humans, there are always potential dangers threatens them. Philosophy, as the oldest systematic way of thinking, seeks to discover what lies behind smartphones. Technology philosophy, which emerged in the modern age, is a branch of philosophy that seeks to examine the nature of technology; ontology, epistemology, and axiology. Based on the thinking of modern philosophers, philosophically, smartphones are not just a means of communication. It changes the way humans understand the world. A world without smartphones is a material world in which people live as living organisms. But, through smartphones, the world changes into digital where everything become possible. It offers various facilities in interacting and exploring the virtual world, offering adventures that cannot be done in the real world. The ease and enjoyment provided by smartphones eventually creates attachment that tends to turn into dependency, problems that must be realized immediately by people so they not to be too complacent in using smartphones in the new normal life.